Prospective associations of vitamin D with β-cell function and glycemia: the PROspective Metabolism and ISlet cell Evaluation (PROMISE) cohort study - Kayaniyil, Sheena; Retnakaran, Ravi; Harris, Stewart B; Vieth, Reinhold; Knight, Julia A; Gerstein, Hertzel C; Perkins, Bruce A; Zinman, Bernard; Hanley, Anthony J (Diabetes (New York, N.Y.), 2011)
To examine the prospective associations of baseline vitamin D [25-hydroxyvitamin D; 25(OH)D] with insulin resistance (IR), β-cell function, and glucose homeostasis in subjects at risk for type 2 diabetes. We followed 489 subjects, aged 50 ± 10 years, for 3 years. At baseline and follow-up, 75-g oral glucose tolerance tests (OGTTs) were administered. IR was measured using the Matsuda index (IS(OGTT)) and the homeostasis model assessment of IR (HOMA-IR), β-cell function was determined using both the insulinogenic index divided by HOMA-IR (IGI/IR) and the insulin secretion sensitivity index-2 (ISSI-2), and glycemia was assessed using the area under the glucose curve (AUC(glucose)). Regression models were adjusted for age, sex, ethnicity, season, and baseline value of the outcome variable, as well as baseline and change in physical activity, vitamin D supplement use, and BMI. Multivariate linear regression analyses indicated no significant association of baseline 25(OH)D with follow-up IS(OGTT) or HOMA-IR. There were, however, significant positive associations of baseline 25(OH)D with follow-up IGI/IR (β = 0.005, P = 0.015) and ISSI-2 (β = 0.002, P = 0.023) and a significant inverse association of baseline 25(OH)D with follow-up AUC(glucose) (β = -0.001, P = 0.007). Progression to dysglycemia (impaired fasting glucose, impaired glucose tolerance, or type 2 diabetes) occurred in 116 subjects. Logistic regression analyses indicated a significant reduced risk of progression with higher baseline 25(OH)D (adjusted odds ratio 0.69 [95% CI 0.53-0.89]), but this association was not significant after additional adjustment for baseline and change in BMI (0.78 [0.59-1.02]). Higher baseline 25(OH)D independently predicted better β-cell function and lower AUC(glucose) at follow-up, supporting a potential role for vitamin D in type 2 diabetes etiology.